Comparison of two approaches to account for GxE interactions in South African Holstein cattle - (:unkn) unknown (My University, 2015)
Comparison of two approaches to account for GxE interactions in South African Holstein cattle. 66. Annual Meeting of the European Federation of Animal Science (EAAP)
Keywords: African Research